Mecanismos de Evolução Cariotípica em Epidendrum L. (Orchidaceae: Epidendroideae) - Assis, Felipe Nollet Medeiros de (2013)
The genus Epidendrum L. comprises approximately 1,500 species of exclusively neotropical distribution, with frequent occurrence of hybridization, polyploidy and asexual reproduction. In addition, some species show complex taxonomy, such as E. secundum, which shows extensive chromosome number variation. This study aimed to test the hypotheses about the causes of chromosome number variability in E. secundum; to investigate the hybrid origin in representatives with intermediate floral morphology between E. flammeum x E. secundum, and between E. xanthinum x E. secundum; and to analyze the heterochromatin diversity and DNA content in species belonging to the subgenus Amphiglottium and Epidendrum. To this end, we performed the quantification of nuclear DNA content by flow cytometry, analysed the heterochromatin distribution using CMA/DAPI fluorochrome banding, and performed the analysis of floral morphology on representatives found in hybridization zones. Mitotic analyzes showed different chromosome counts ranging from 2n = 24 in E. fulgens to 2n = 224 in E. cinnabarinum, with metacentric, submetacentric and acrocentric chromosomes in all species. CMA+/DAPI¬ pericentromeric and terminal chromosome regions, and some CMA¬/DAPI+ and CMA0 terminal regions were identified, with variation in size, number and position. Pericentromeric regions generally was CMA0/DAPI¬ in most species. The leaf tissues of all specimens examined presented one or two endoreduplication cycles. To 18 populations of E. secundum analyzed, 16 presented diploid individuals, with an average of 2C = 4.08 pg DNA, and in two populations were identified tetraploid individuals, with an average of 2C = 8.24 pg DNA. In some populations were identified cytotypes with B chromosomes in variable number, sometimes entirely CMA+/DAPI¬. In relation to putative hybrid analysis, three hybrid zones were investigated. In São João do Tigre (PB), E. flammeum presented 2n = 50 and 2C = 5.04 pg DNA, E. secundum presented 2n = 62 chromosomes and 2C = 4.82 pg DNA. Hybrid individuals had 2n = 56, with 2C = 4.63 pg DNA. In Nova Friburgo (RJ), E. xanthinum presented 2n = 28 with 2C = 4.48 pg DNA. The specimens of E. secundum in this population presented 2n = 56 and 2C = 3.68 pg DNA. The putative hybrids presented 2n = 42 with 2C = 4.37 pg DNA. The Principal Component and Cluster Analysis confirmed the intermediate nature of floral morphology among putative hybrids and possible parents. Despite the occurrence of different chromosome numbers in E. secundum, populations showed no significant DNA content variation by Tukey test, suggesting that the increase in the number of acrocentric chromosomes is mainly caused by centric fissions. High levels of reproductive compatibility suggest that hybridization and introgression are important in early stages of speciation in Epidendrum. Karyological diversification observed seems related to disploid and polyploid events, whose changes in fundamental number may be the result of complex intra and intergenomic reorganizations.